Playing with Noah's Animals: A Theological Analysis of Four Retro Video Games Called Noah's Ark - Bosman, Frank (Journal for religion, film and media, 2023)
A special genre has emerged in video games - Bible games. As a subset of the broader genre of Christian games - aimed at providing age- and faith-appropriate content for religious audiences and/or proselytizing non-believers to the Christian faith - the Bible games gamify their inspirational source material. Frequently, these games are considered inferior ("bad") games, usually because of the ludonarrative dissonance in terms of gameplay and narrative. This article discusses four of these supposedly bad Bible games, all from the 1980s and 1990s and all using the biblical story of Noah's ark as source material: Noah's Ark by Enter-Tech (1982), the NES games Noah's Ark (as a part of Bible Adventures) by Wisdom Tree and Noah's Ark by Konami (1992), and finally the SNES game Super Noah's Ark 3D by Wisdom Tree again. The article provides an overall comparison and analysis of the four in theological terms.